Enzymatic Pretreatment of Slaughterhouse Wastewater: Application of Whole Lipolytic Cells of Rhizopus oryzae Produced from Residual Vegetable Oil - Reis, Willian S. M.; Bento, Heitor B. S. [UNESP]; Carvalho, Ana K. F.; Pereira, Ernandes B. (MDPI, 2024)
This study assessed the application of whole lipolytic cells in the pretreatment of slaughterhouse wastewater to reduce its lipid content. The fungal biomass of Rhizopus oryzae was evaluated in the hydrolysis of slaughterhouse wastewater containing high lipid concentrations, focusing on the biomass’s concentration and the effect of using an emulsifier and surfactant. The use of the whole-cells lipase of Rhizopus oryzae grown in a residual vegetable oil medium proved effective in the hydrolysis of slaughterhouse wastewater, generating concentrations of free fatty acids (FFA) ranging from 40.36 to 90.14 mM. The action of lipase in the hydrolysis of slaughterhouse residues indicated its effectiveness in pretreating lipid-rich liquid residues, potentially boosting the microbiota of this anaerobic treatment. The results showed that lipase activity without surfactant exhibited a similar performance to that of Triton X-100 in the hydrolysis of liquid residues. However, the combination of lipase and surfactant could represent a promising strategy to optimize free fatty acid production from slaughterhouse residues, strengthening anaerobic treatment processes and potentially enhancing the overall efficiency of waste management systems.
Keywords: hydrolysis; lipase; whole cell